2008
DOI: 10.3200/socp.148.2.187-209
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Relational Demographics on Perceived Managerial Trustworthiness: Similarity or Norms?

Abstract: Perceived trustworthiness is a critical antecedent of interpersonal trust, yet researchers have a limited understanding of how such perceptions are generated. The authors used 2 competing perspectives within the relational demography literature--similarity-attraction and relational norms--to empirically examine the effect of demographic differences. Whereas the similarity-attraction account suggests that subordinates will perceive their managers as more trustworthy when managers and staff are similar in demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 48 publications
2
50
0
Order By: Relevance
“…Work tenure is a reflection of experience and knowledge in the organization (Lau, Lam, & Salamon, 2008). As an individual's career unfolds in a company, his or her job knowledge, skills, abilities, and confidence increase.…”
Section: Tenure As a Moderatormentioning
confidence: 99%
“…Work tenure is a reflection of experience and knowledge in the organization (Lau, Lam, & Salamon, 2008). As an individual's career unfolds in a company, his or her job knowledge, skills, abilities, and confidence increase.…”
Section: Tenure As a Moderatormentioning
confidence: 99%
“…The results revealed a curvilinear relationship, such that perceived trustworthiness was maximized at the midpoint, with the most typical face. Third, Lau, Lam, and Deutsch Salamon (2008) examined the effects of employee-manager demographics on the perceived trustworthiness of the manager. Rather than trustworthiness being maximized with shared demographics in dyads, trustworthiness was maximized when the manager had a typical demographic profile.…”
Section: Study 1: Theory Developmentmentioning
confidence: 99%
“…Liden et al (1993) showed that demographic similarity between supervisors and employees had no significant effects on the quality of this relationship over time, whereas others found that demographic similarity between supervisors and employees had a positive effect on mutual liking (e.g., Tsui & O'Reilly, 1989). We, therefore, also include surface-level fits in our study, such as fit with regard to gender (e.g., Vecchio & Brazil, 2007), age (e.g., Shore, Cleveland, & Goldberg, 2003) and educational level (Lau, Lam, & Salamon, 2008). Moreover, we incorporate a specific type of fit (guanxi) that is relevant in Chinese cultures.…”
Section: Supervisor Ps Fit Perceptionsmentioning
confidence: 99%